Optimizing the bandwidth of plate-type acoustic metamaterials - Felix Langfeldt and Wolfgang Gleine (The journal of the Acoustical Society of America, 2020)
Plate-type acoustic metamaterials (PAM) consist of a thin film with multiple periodically attached masses. Although these metamaterials can be very lightweight and thin, the resulting sound transmission loss at low frequencies can be much larger than the corresponding mass-law. This is a result of anti-resonances at which the sound transmission through the PAM is strongly reduced. One general challenge, however, is that the anti-resonances are only very narrowband. This makes the application of PAM to noise control problems with broadband noise sources or changing tonal sources difficult. In this contribution, different design strategies to improve the bandwidth of PAM for low-frequency noise control applications (multiple masses per unit cell or stacking multiple PAM layers) are evaluated using optimizations. An efficient modal based model is employed to represent the PAM using their eigenfrequencies and modal masses. The model is validated using simulations and experimental measurements. The optimization results show that it is possible to significantly improve the bandwidth of PAM using the investigated design strategies. In fact, it is shown that the same bandwidths can be achieved either using multiple masses or multiple PAM layers. This allows for some flexibility in the design of suitable noise control treatments with PAM.